Smart Finance- The Involvement of Artificial Intelligence in FinTech - Dr. Pooja. Srivastava, Ragini Dixit, Eti Agarwal, (European Economic Letters (EEL), 2025)
The Financial industry has transformed due to growth of FinTech. It gives hike to new opportunities for better customer experience, investment strategies and risk management. The game-changer behind this revolution is Artificial Intelligence (AI). The research paper analyzes the involvement of Artificial intelligence in financial service industry. The research paper is exploring 3 focal areas of AI in fintech- Algorithm trading, Predictive analytics and robo-advisors for smart investment. The paper includes these technologies, their impact and their implementation in financial industry. This paper Illustrates how AI is changing and re-shaping the future of finance by giving smarter investment opportunities.